Oleksandr Popov (1855–80) and the Reconstruction of Indo-European Noun Inflection. (2nd July 2016) - Danylenko, Andrii
Abstract: This paper aims to ascertain the place of the Ukrainian linguist Oleksandr Popov (1855–80) in the history of Indo-European and typological studies. Remaining largely unknown in the west, Popov left a trailblazing contribution to the reconstruction of IE noun inflection. Critical of Curtius' approach nourished by the idea of linguistic absolutism, Popov offered a systematic analysis of the accusative, nominative, and vocative cases taken in their interdependency. In view of the interchangeability of the independent accusative and the independent nominative, Popov argued that the accusative case might have emerged before the vocative and even prior to the nominative, with a possibility of the nominative arising before the accusative. The Ukrainian linguist based his reconstruction on the distinction between the 'active' and 'passive' entities encoded by the nominative in * - s and the accusative in * - m respectively, thus anticipating discussion of the active typology of Proto-IE in the 20th century. By providing a detailed survey of Popov's theory, the author highlights its pioneering character in the light of modern comparative-historical and typological views.